Cyclic loading tests of RC columns strengthened with high ductile fiber reinforced concrete jacket. (30th October 2017) - Deng, Mingke; Zhang, Yangxi
Highlights: The HDC jacket effectively changed the brittle failure mode of RC columns. No diagonal cracks occurred on the bar mesh reinforced HDC jacket. The seismic response of the RC columns was remarkably improved by HDC jacket. Bar mesh reinforced HDC jacket can be used to strengthen the high axial load columns. Abstract: High ductile fiber reinforced concrete (HDC) is characterized by its tensile strain-hardening behavior and high compressive strain ability. This paper investigates the seismic performance of reinforced concrete (RC) columns strengthened with HDC jacket, eight RC columns were designed and six of them were strengthened with HDC jacket or bar mesh reinforced mortar (BMRM) jacket. The influence of jacketing schemes and axial load ratio on the failure modes, hysteresis loops, skeleton curves, deformation capacity and energy dissipation capacity is analyzed respectively. The experimental results from lateral cyclic loading tests on the specimens show that the failure mode of the columns could be changed from brittle to ductile under the confinement effect of the HDC jackets. The HDC jacket without bar mesh was certified to be more effective than the BMRM jacket in improving the plastic deformation capacity of the original columns. The HDC jacket with bar mesh is the best strengthening scheme, the columns jacketed by which exhibited tremendously enhancement in drift capacity and energy dissipation capacity by developing plastic hinges in the column foot even when the column was under high axial load ratio.